MARKETING STRATEGY: INCREASE SALES ON INDEPENDENT BUSINESS THROUGH DIGITAL MARKETING - Darmawan; Sarah Bhiba (ASIAN PUBLISHER, 2022)
In an effort to increase sales of good consumables such as perfume, it requires a strategy that is carried out by increasing advertising and promotion through digital marketing such as on social media Instagram which plays an important role in attracting the attention of consumers who currently buy more online. Strategies developed in increasing sales such as segmenting, targeting, positioning which in this important case is to maintain good relationships betweencustomers and sellers, in addition to the physical efficiency factor as a form of consequence that must be followed during the sales increase process takes place. SWOT analysis is needed to be able to see the business environment where the marketing mix plays an important role in overcoming the obstacles that occur. As a strategy in increasing sales of Consumables Good Premium Bekasi by segmenting, targeting, positioning, it can overcome obstacles where the advertisements displayed are less attractive to customers so that the choice of advertising and promotion designs must be made more as an option to communicate well with customers.